QUALITY CONTROL ANALYSIS WITH SIX SIGMA-DMAIC METHOD IN EFFORT REDUCE NUMBER OF SUGAR PRODUCTS AT PT. PG. GORONTALO (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
Companies need to maintain and improve the quality of products derived by applying a good quality control, because quality is an important factor in improving satisfaction and loyalityas consumers, as well as PT. PG .Gorontalo ; Six Sigma methods that have high discipline can help develop and deliver near-perfect products. The purpose of this study was to determine how the value of sigma PT .PG . Gorontalo and what factors of product defects. In this analyzis , researchers took 3 months of data production and analyze the Six Sigma DMAIC method. Researchers examined / analyzed using a questionnaire and the report of production to help get the material of analyzis. From this research , it has been showed that the presence of defects of products in the production process of PT. PG. Gorontalo at 5.664, 72 DPMO. It is also known that the cause is the human factor , machines, methods, materials, and environment. Based on these results , we can conclude that the value of sigma PT. PG. Gorontalo is located at 4 to 4.5 sigma, the factor most dominant cause of disability is due to lack of proper vacuum pressure